REVIEW 100 HARI KEPEMIMPINAN PRESIDEN JOKO WIDODO TERHADAP KEBIJAKAN EKONOMI POLITIK INDONESIA DI MATA INTERNASIONAL - Dahlan Panjaitan; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses the Jokowi 100 days as president. As president of the transition Jokowi got challenges and tests from the previous administration whether it economic and political problems. Challenges in the region emerged from the ASEAN economic community is also the challenge of the international community such as the World Bank, economic growth and diplomatic relations Indonesia.For that Jokowi as transitional president of Indonesia should have and promote rational choices most priority to the interests of the nation. Therefore, this study uses analysis of rational choice theory and behavior, which is a qualitative research method. Indonesia is a big country and requires a lot of attention and care.Therefore, measures taken by the government Jokowi considered relevant but also extreme for neighboring countries. Such a policy "sea toll", Asia shaft, sunk thieves alien fish, deportation, and other policies.Key Words: Economic And Political Policies, President Joko Widodo, Governance Challenges, International Respons To Indonesian Government.